Biografi Tun Sakaran Dandai : min rilaut ni bud - Baszley Bee b. Basrah Bee; Md. Saffie Abdul Rahim, 1977-; Sabihah Osman (Penerbit Universiti Malaysia Sabah, 2015)
Biography of Tun Sakaran Dandai, a politician in Sabah.